Reversibilitas Reaksi Elektrokimia pada Elektroda Superkapasitor Zeolit Berbasis Silika Sekam Padi yang Dikalsinasi pada Suhu 450, 550, dan 650? - Fatia Ulfah; S Suprihatin; Posman Manurung (Jurnal Teori dan Aplikasi Fisika, 2017)
Zeolite based silica rice husk has been prepared at temperature of 450, 550, and 650?. This research was conducted to study the effect of calcination temperature in forming of crystalline phases and standard electron rate constant (k0). The zeolite K450 was formed quartz and bohmite phases, zeolite K550 and K650 was formed cristobalite, stishovite, gamma-alumina, and natrolite phases. Electrochemical reaction of zeolite K450, K550 and K650 are irreversible. Peak potential oxidation-reduction is between 240 mV and 390 mV. The higher value of calcination, the higher value of k0. The k0 value of zeolite K450, K550, K650 at scan rate of 1 V/s are 29,658 x 10-9; 36,398 x 10-9; 77,110 x 10-9 cm/s respectively. Natrolite phase of zeolite K550 and K650 have changed zeolite charge be netral. Based on these result, value k0 of zeolite K550 and K650 are going to be a reversible.